A systematic review of effects and complications after transsphenoidal pituitary surgery: endoscopic versus microscopic approach. Issue 6 (1st December 2020) - Li, Kai; Zhang, Jun; Wang, Xin-Sheng; Ye, Xun; Zhao, Yuan-Li
Abstract: Background: Microscopic transsphenoidal surgery (MTS) has been considered as the gold standard for transsphenoidal pituitary surgery, but nowadays endoscopic transsphenoidal surgery (ETS) has become popular due to its wide view and improved lighting. Material and methods: The electronic databases were systematically searched, and the meta-analyses of the eligible studies that evaluated endoscopic versus microscopic methods in patients with pituitary surgery were conducted with Review Manager 5.0. The primary outcomes included visual improvement, gross tumor removal (GTR), cerebrospinal fluid (CFS) leak, diabetes insipidus (DI), other complications, and length of hospital stay. The Egger's test was conducted to estimate possible publication bias. Results: In total, 13 articles eventually met the inclusion criteria. The meta-analyses suggested that the differences with regard to visual improvement, overall complication rate, GTR, CSF leak, diabetes insipidus (DI), meningitis, visual impairment, syndrome of inappropriate antidiuretic hormone secretion (SIADH), new onset hypopituitarism, and hypothyroidism between the endoscopic and microscopic groups were not statistically significant. The length of hospital stay was much longer with the microscopic approach when compared with the endoscopic method. Conclusion: The endoscopic and microscopic approaches show similar effects and complication rates. The endoscopic technique could be adopted as a reasonable alternative in pituitary surgery.